Penanaman Nilai Karakter pada Anak Usia Dini melalui Pembelajaran Berbasis Musik dan Lagu Model - Purwanto, Setyoadi (THUFULA, 2015)
Singing is an activity that can not be separated from the world ofeducation in kindergarten. Every day, students in kindergarten or RaudlatulAthfal there is always a singing activity. Learning atmosphere feels moreexcited, if students are invited to sing along. It is inevitable that singing is avery effective medium to instill positive characters, such as honest, disciplined,creative, independent, love peace, love reading and love of the homeland. Thisis in accordance with the concept of edutainment learning, which is an attemptto find common ground educational and entertainment world, especially onthe level of RA / TK.